53 Treatment intensity of high- and very high-risk patients for the prevention of cardiovascular events: baseline characteristics from the Irish cohort of the multinational observational Santorini study. (6th October 2022) - Rai, H; Sheahan, R; Murphy, R; McGovern, L; McFadden, E; Murphy, A; Nolan, D; Colleran, R; Byrne, RA
Abstract : Introduction: Lower goals for low-density lipoprotein cholesterol (LDL-C) are recommended for patients with high and very high cardiovascular (CV) risk according to ESC/EAS 2019 guidelines. Real-world studies in Europe have previously demonstrated suboptimal achievement of ESC/EAS guideline LDL-C goals. SANTORINI is the first European observational study since the 2019 guidelines to assess whether management of high- and very high-risk patients has improved since recent guideline updates. We report baseline patient characteristics and lipid lowering therapy (LLT) treatment patterns in patients recruited in the SANTORINI trial at investigational sites in Ireland. Methods: SANTORINI is a multinational, multicentre, prospective, observational, non-interventional study conducted in 14 European countries (clinicaltrials.gov identifier: NCT04271280 ). Patients aged ≥18 years assessed at high and very high risk and requiring LLT were recruited across primary and secondary care settings. The present analysis focuses on patient characteristics, medical history, current LLT and other concomitant medications of patients enrolled at 6 investigational sites in Ireland. Twelve-month follow-up is ongoing. The SANTORINI study was funded by Daiichi-Sankyo Europe. Results: Amongst a total of 100 patients recruited during May 2020 to Jan 2021, most cases were classified as very high risk (65%). 52% of cases were classified based on clinical experience, with 47% classified as per ESC/EAS guidelines. Overall, 19% of cases were not receiving any LLT at baseline, 74% were receiving LLT-monotherapy (73% on statin monotherapy, 1% on other LLT-monotherapy). Combination therapy with statin plus ezetimibe was used in 5% of patients with other LLT combinations in 2%. LDL-C levels at baseline in the total cohort was 2.08±0.96 mmol/L, with lower values in very high risk cases as compared to high risk cases (1.90±0.85 and 2.39±1.05 mmol/L respectively). Demographics, cardiovascular risk factors, prevalence of atherosclerotic cardiovascular disease, as well as proportions of patients receiving different LLT regimens in the total cohort as well as in the high and very high risk subgroups are shown in figure 1 . Conclusion: In the current analysis ESC/EAS guidelines are not the most frequently used tool for risk classification. Mean LDL-C levels both in high and very high risk patients are higher than the recommended goals and the prevalence of combination LLT therapy was low. Intensification of LLT in high and very high risk patients seem to be an unmet need in routine clinical practice in Ireland.